2013
DOI: 10.1007/s00382-013-1777-x
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric ozone depletion: a key driver of recent precipitation trends in South Eastern South America

Abstract: On a hemispheric scale, it is now well established that stratospheric ozone depletion has been the principal driver of externally forced atmospheric circulation changes south of the Equator in the last decades of the 20th Century. The impact of ozone depletion has been felt over the entire hemisphere, as reflected in the poleward drift of the midlatitude jet, the southward expansion of the summertime Hadley cell and accompanying precipitation trends deep into the subtropics. On a regional scale, however, surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
84
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 44 publications
(60 reference statements)
6
84
0
5
Order By: Relevance
“…Several previous studies have linked both interannual and longer decadal variations in the SAM to temperature changes elsewhere in the SH (Thompson and Solomon 2002;Gillett and Thompson 2003;Gillett et al 2006;Manatsa et al 2013) and with cooler conditions in the summer over much of eastern Australia (Hendon et al 2007;Meneghini 2007). More recent modeling and observational studies have shown that ozone depletion can affect both mean and extreme rainfall in the southern subtropics, with enhanced precipitation in Australia and South America in the austral summer (Kang et al 2011;Fyfe et al 2012;Kang et al 2013;Gonzalez et al 2014). The positive SAM trend reflects a poleward shift of the extratropical jet and accompanying storm tracks (Archer and Caldeira 2008) and a poleward shift of the edge of the Hadley cell (Hu and Fu 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Several previous studies have linked both interannual and longer decadal variations in the SAM to temperature changes elsewhere in the SH (Thompson and Solomon 2002;Gillett and Thompson 2003;Gillett et al 2006;Manatsa et al 2013) and with cooler conditions in the summer over much of eastern Australia (Hendon et al 2007;Meneghini 2007). More recent modeling and observational studies have shown that ozone depletion can affect both mean and extreme rainfall in the southern subtropics, with enhanced precipitation in Australia and South America in the austral summer (Kang et al 2011;Fyfe et al 2012;Kang et al 2013;Gonzalez et al 2014). The positive SAM trend reflects a poleward shift of the extratropical jet and accompanying storm tracks (Archer and Caldeira 2008) and a poleward shift of the edge of the Hadley cell (Hu and Fu 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Kirchner and Peters 2003;Peters et al 2015) compared to zonally symmetric ozone variations. In many long-term General Circulation Model simulations, a prescribed time series of zonal mean ozone is employed (Cagnazzo et al 2006;Cionni et al 2011;Szopa et al 2013;Gonzalez et al 2014;Xie et al 2016Xie et al , 2017 and the ZAO heating effects, which have an important contribution to chemical-radiative-dynamical feedbacks (e.g. Sassi et al 2005;Nathan and Cordero 2007;Gabriel et al 2007Gabriel et al , 2013McCormack et al 2011;Peters et al 2015), are not properly considered.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, the most significant changes in southern hemisphere climate have included [Canziani et al, 2014]: (1) a southward shift and intensification of the tropospheric eastward jet over the Southern Ocean region-resulting in a tendency for the extratropical storm tracks to move poleward; (2) anomalously dry conditions have occurred over southern Australia, New Zealand and southern South America, and anomalously wet conditions over northwestern Australia and South Africa; (3) a warming of the Southern Ocean and its waters have become less saline; (4) a warming of the Antarctic Peninsula and its oceanic margins; (5) an expansion the tropical zone and a shift of atmospheric mass from mid to higher latitudes (Hendon et al, 2007;Calvo et al, 2012;Gonzalez et al, 2013;Turner et al, 2013);and (6) an increase in Antarctic average sea-ice extent. These changes are largely consistent with industrial era effects expected from increasing levels of anthropogenic greenhouse gases and the more recent effects caused by ozone depletion, and are largely though not exclusively related to observed changes in the meridional location of the mid-latitude tropospheric jet during recent decades (Lin et al, 2009;Fu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%